Political Connections, Board Gender Diversity, and Institutional Ownership on Tax Avoidance - Pontoh, Joseph Febian; Kustinah, Siti (Jurnal Akuntansi, 2024)
Purpose - This study aims to analyze the influence of Political Connections, Board Gender Diversity, Institutional Ownership on Tax Avoidance. Design/methodology/approach - The research method is quantitative using secondary data. The population used is the Property and Real Estate sector companies listed on the IDX (Indonesia Stock Exchange) for 2018-2022 period. Sampling technique used purposive sampling, obtained 70 observation data. Data analysis techniques using multiple linear regression analysis, correlation coefficient, coefficient of determination, t test, f test using SPSS 26 software. Findings - Based on the results of research and discussion, it shows that Political Connections, Board Gender Diversity, Institutional Ownership have a significant partial and simultaneous effect on Tax Avoidance. Research limitations/implications - The first research limitation, the sector used in this study is just one of those that is listed on the IDX, while there are still many sectors that are not used. Second, the study period is limited to five years. Third, many other variables that can affect tax avoidance are not examined in this study. Keywords: Political Connections, Board Gender Diversity, Institutional Ownership, Tax Avoidance